MEMBANGUN PENGALAMAN BELAJAR YANG MENYENANGKAN: OPTIMALISASI FAKTOR-FAKTOR PENENTU KEPUASAN PESERTA PELATIHAN - Anwar, Rinawati; Naily Kamaliah (Komunitas Manajemen Kompetitif, 2024)
Abstract: This study aims to evaluate and analyze factors and aspects that influence participants' satisfaction in a training that equipped with LMS. As an effort to build fun learning, the study identifies the supporting aspects in training that need to be improved to enhance the quality and service of training. The research classifies as a quantitative research where the data collection was carried out using an online questionnaire that was distributed to all participants in the statistical and data analysis training. Data processing was carried out using SPSS 26 and the results were analyzed with descriptive analysis and inferential analysis using multiple regression methods and factor analysis (with varimax rotation). The results of the study shows that overall participants were satisfied with the training services. The Ease of Access and Navigation aspect in the LMS is considered as the best performance aspects among other aspects. Meanwhile, the regression analysis shows that Learning Media and LMS Visual Design aspect has a significant effect on participant’s satisfaction, while Training Materials and Ease of Access to LMS aspect does not give any notable effect. The results indicate that participants would more appreciate an interactive learning methods and attractive visual designs in a training. Several efforts on improvement that necessary in order to enhance the performance and quality of the training services in the future are providing a more flexible and segmented curriculum, developing various learning media, and improving the LMS visual design for better participant’s understanding and learning experience.